2022
DOI: 10.1111/cas.15688
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of myeloid signature genes for predicting prognosis and immune landscape in Ewing sarcoma

Abstract: Myeloid cells as a highly heterogeneous subpopulation of the tumor microenvironment (TME) are intimately associated with tumor development. Ewing sarcoma (EWS) is characterized by abundant myeloid cell infiltration in the TME. However, the correlation between myeloid signature genes (MSGs) and the prognosis of EWS patients was unclear. In this research, we synthetically characterized the expression of MSGs in a training cohort and classified EWS patients into two subtypes. Immune cell infiltration analysis rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…The tumor microenvironment (TME) plays a key role in tumor and developmental processes and therapeutic susceptibility, and the typical immune profile of ES is a large infiltration of myeloid cells in the TME [ 34 , 35 ]. Myeloid-derived suppressor cells (MDSCs) are involved in a variety of immunosuppressive responses as immature monocytes and granulocytes, and Zhang et al [ 36 ] identified a subpopulation of MDSCs with significant immunosuppressive effects.…”
Section: Discussionmentioning
confidence: 99%
“…The tumor microenvironment (TME) plays a key role in tumor and developmental processes and therapeutic susceptibility, and the typical immune profile of ES is a large infiltration of myeloid cells in the TME [ 34 , 35 ]. Myeloid-derived suppressor cells (MDSCs) are involved in a variety of immunosuppressive responses as immature monocytes and granulocytes, and Zhang et al [ 36 ] identified a subpopulation of MDSCs with significant immunosuppressive effects.…”
Section: Discussionmentioning
confidence: 99%
“…M1 macrophages are generally polarized by interferon-gamma, secrete large amounts of pro-inflammatory factors, and play an essential role in the early stages of inflammation. M2 macrophage express suppressive inflammatory factors that inhibit the inflammatory response and tissue repair ( 34 , 35 ). Watson et al.…”
Section: Discussionmentioning
confidence: 99%
“…M1 macrophages are generally polarized by interferon-gamma, secrete large amounts of pro-inflammatory factors, and play an essential role in the early stages of inflammation. M2 macrophage express suppressive inflammatory factors that inhibit the inflammatory response and tissue repair (34,35). Watson et al (69) showed that M1 macrophage were essential mediators of virus-induced myopathy and that blocking SHP-1 activation in macrophages could prevent virus-induced myofiber degeneration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the large absolute number of survivors of the pandemic in these years, there are increasing reports of long COVID (21). Bioinformatics analysis as an emerging technology can integrate and analyse biological data to facilitate the researcher to understand better the common mechanism between different illnesses and make effective countermeasures (22)(23)(24). For example,…”
Section: Introductionmentioning
confidence: 99%